Multi-Detector Computed Tomography Angiography of a Ruptured Giant Renal Angiomyolipoma with Pseudoaneurysmand Associated Saccular Dilatation of Left Renal Artery - parashari, umesh chandra; khanduri, sachin; bhadury, samarjit; singh, gaurav (Urology Journal, 2014)